Extreme downsizing of spin crossover nanoparticles towards stable colloids in water: a detailed nano-topographic study. Issue 43 (1st November 2021) - Polyzou, Christina D.; Malina, Ondřej; Polaskova, Michaela; Tripathi, Manoj; Dalton, Alan B.; Parthenios, John; Tangoulis, Vassilis
Abstract : The extreme downsizing effect on 2D SCO nanoparticles resulted in a two-step hysteretic behavior and stability in aqueous dispersions. Abstract : The investigation and elaboration of the spin-crossover (SCO) phenomenon in two-dimensional (2D) Hofmann-type nanosized SCO materials and the size-reduction effect on the cooperativity and thermodynamic properties of the nanoparticles are still in progress. Liquid phase exfoliation (LPE) as a top-down experimental protocol for the fabrication of 2D SCO atomically thin nanosheets is also an underexplored area of research. Given the increasing scientific interest for 2D nanosheets and their unique thickness-dependent electronic properties, the above-mentioned study is of utmost importance. In this context, we present a detailed nano-synthetic study based on the reverse-micellar synthesis of [Fe II (2-mpz)2 Ni(CN)4 ] and further rationalization of this method followed by LPE experimental protocols in order to synthesize nanoparticles with well-controlled sizes and shapes. The role of concentration and reaction temperature is investigated with respect to the size, dispersion, morphology and magnetic properties of the nanoparticles. It was found that for specific values of these parameters, the synthesis of nanoparticles is controlled and the final products are nanoparticles with an agglomerated architecture. According to an extensive atomic force microscopy (AFM) nano-topographic study, this agglomeration is best described as right truncated thick prisms of [Fe II (2-mpz)2 Ni(CN)4 ] stacked in a vertical position on a rectangular base plate. During the LPE procedure and by prolonging the sonication period, the thick prisms are detached and, eventually, exfoliated to atomically thin right prisms of height ∼1 nm. Magnetic measurements revealed that the size reduction leads to the progressive downshift of abrupt thermal hysteresis with two-step SCO transition temperatures of the bulk [Fe II (2-mpz)2 Ni(CN)4 ] material to a gradual incomplete SCO behavior of an almost single-layer 2D [Fe II (2-mpz)2 Ni(CN)4 ] nanosheet.